2006
DOI: 10.1007/s00701-006-0877-3
|View full text |Cite
|
Sign up to set email alerts
|

Spinal brucellosis: Turkish experience based on 452 cases published during the last century

Abstract: Based on this critical review of literature from Turkey, it is concluded that early diagnosis and correct management are important to prevent the harmful effects of brucellosis and its complications, and that the treatment of choice is antibiotic therapy alone in most cases of brucellosis involving the spine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
78
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 48 publications
4
78
0
8
Order By: Relevance
“…In the chronic phase the disease is characterized by various organ-related manifestations, bones and nerves [1]. It has been reported that skeletal manifestations are more frequent and more evident during the chronic and subacute stages [8,22,25,26]. According to Capasso in the initial phase there is a characteristic brucellar polyserositis with a pleural, peritoneal or pericardial seat [1].…”
Section: Skeletal Pathology and Differential Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…In the chronic phase the disease is characterized by various organ-related manifestations, bones and nerves [1]. It has been reported that skeletal manifestations are more frequent and more evident during the chronic and subacute stages [8,22,25,26]. According to Capasso in the initial phase there is a characteristic brucellar polyserositis with a pleural, peritoneal or pericardial seat [1].…”
Section: Skeletal Pathology and Differential Diagnosismentioning
confidence: 99%
“…Brucellosis is divided according to its duration into acute (less than 2 months), subacute (2-12 months), and chronic form (more than 12 months) [8]. Primary infection typically manifests as chronic respiratory illness, fever and splenomegaly [7].…”
mentioning
confidence: 99%
“…Radiculopaty was most frequent neurological finding and spondylitis or spondylodiscitis was the predominant radiological finding. MRI was found to be more sensitive in detecting the presence of spondylodiscitis than other imaging modalities [12].…”
Section: Discussionmentioning
confidence: 92%
“…Spinal brucellosis originates through a haematogenous route and infection usually initiates from the anterior superior endplate of a vertebra corpus due to the rich supply of blood in this area [1,2]. Inflammation can then distribute to the entire vertebral body or to the intervertebral disc, causing spondylodiscitis.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation can then distribute to the entire vertebral body or to the intervertebral disc, causing spondylodiscitis. Literature regarding nerve root compression in brucellar spondylodiscitis involves complications such as epidural abscess, granuloma or discitis secondary to vertebral body involvement by brucellosis [1][2][3]. Brucellosis discitis as an infectious etiology of spinal root compression is uncommon.…”
Section: Discussionmentioning
confidence: 99%